Preparation and the Catalytic Properties of Attapulgite / TiO2 Nanocomposites. Issue 1 (January 2022) - Shang, Jianping; Li, Tao; Qin, Xiaoping; Zhao, Bin; Li, Xuefei
Abstract: With the rapid development of industry, the discharge of textile printing and dyeing wastewater will cause serious pollution to other pure water bodies. It is imperative to deal with textile printing and dyeing wastewater. In this paper, with titanium tetrachloride as a precursor, attapulgite (ATP) / TiO2 nanocomposites were prepared by a neutralizing hydrolysis method and their catalytic activities were investigated by the oxidative degradation of methylene blue dye using ozone as oxidant. The test results showed that there were significant interactions between TiO2 and ATP support. The effects were also studied of ozone concentration, catalyst amount, reaction temperature, and initial concentration of methylene blue on the degradation rate of methylene blue catalyzed by the prepared attapulgite / TiO2 nanocomposites, and under the optimal conditions, the methylene blue could be degraded more than 90% in 30 minutes. Compared with that of pure ATP, the catalytic activities of ATP / TiO2 nanocomposites were enhenced remarkably. The degradation mechanism of methylene blue was also discussed.